DIDACTIC PROPOSAL FOR THE TEACHING OF CELLULAR BIOLOGY IN FUNDAMENTAL TEACHING: THE HISTORY OF SCIENCE, EXPERIMENTATION AND INCLUSION - Wommer, Fernanda Gabriela Bitencourt; Michelotti, Angela; Loreto, Elgion Lúcio da Silva (Cadernos de Educação Tecnologia e Sociedade, 2019)
The first general competence described in the National Curricular Common Base emphasizes the importance of the valorization and use of historically constructed knowledge about the world, recognizing the importance of teaching about the History and Nature of Science. These are fundamental components for a scientific school formation, where along aspects related to the theme of inclusion, potentiate the teaching process, allowing a greater interaction between science - classroom - students. In this proposal our objective is to guide, collaborate and facilitate the teaching of Cell Biology in the final years of elementary school, through a didactic sequence called "Knowing the history of cell discovery", "Knowing cells through didactic models" and "Building a Microscope", the methodology used was based on the researches developed by the authors in their dissertations in the area of Science Education, seeking to answer the following research problem "How to make scientific concepts about the teaching of cellular biology exceed the students' ability to abstract and become understandable?". Since many times the teaching of Cell Biology happens in a theoretical way and without contextualization, and because it is difficult to understand due to the high degree of abstraction of the students, we propose the didactic sequences to facilitate the teaching and learning of this subject. Each of these actions will be developed through active learning methodologies, valuing student participation and making them think about what they are learning. The use of the didactic sequence proposed in the teaching of Cell Biology uses the active methodologies, providing the students to awaken through the microscopic world, in a playful and fun way, providing students with active agents in their teaching and learning process.